2010
DOI: 10.1038/cgt.2009.88
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti-oncomirs miR-143 and -145 in human colorectal tumors

Abstract: We examined the expression levels of microRNAs (miRNAs (miRs)) in colorectal tumors (63 cancer specimens and 65 adenoma specimens) and paired non-tumorous tissues. Decreased expression of miR-143 and -145 was frequently observed in the adenomas and cancers tested, compared with miR-34a downregulation and miR-21 upregulation. Expression profiles of miR-143 and -145 were not associated with any clinical features. As the downregulation of miR-143 and -145 was observed even in the early phase of adenoma formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
179
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(188 citation statements)
references
References 25 publications
9
179
0
Order By: Relevance
“…Overexpression microRNA-143 regulates MLL-AF4 oncogene expression L Dou et al of miRNAs can result in downregulation of tumor suppressor genes, whereas their decreased expression can lead to oncogene upregulation. Expression of miR-143 was previously shown to be reduced in colon cancer and various cancer cell lines (Akao et al, 2007;Akao et al, 2010). In this study, miR-143 was significantly downregulated in samples from MLL-AF4 B-cell ALL patients compared with healthy individuals.…”
Section: Discussionmentioning
confidence: 48%
“…Overexpression microRNA-143 regulates MLL-AF4 oncogene expression L Dou et al of miRNAs can result in downregulation of tumor suppressor genes, whereas their decreased expression can lead to oncogene upregulation. Expression of miR-143 was previously shown to be reduced in colon cancer and various cancer cell lines (Akao et al, 2007;Akao et al, 2010). In this study, miR-143 was significantly downregulated in samples from MLL-AF4 B-cell ALL patients compared with healthy individuals.…”
Section: Discussionmentioning
confidence: 48%
“…1B). MiR-145, as a positive control, was known to have potent antiproliferative activity in colorectal cancer (21)(22)(23). miR-124, miR-137 or miR-145 inhibited the growth of HCT116 cells.…”
Section: Growth Inhibition Of Colorectal Cancer Cells By Mir-124 Mirmentioning
confidence: 99%
“…The ectopic expression of miR-145 in such cells exhibits a growth inhibitory effect [1,18]. In human malignant melanoma (HMM), it is suggested that a higher expression level of miR-145 is associates with longer survival after recurrence [19].…”
mentioning
confidence: 99%